2016
DOI: 10.1111/irj.12135
|View full text |Cite
|
Sign up to set email alerts
|

The decision to moonlight: does second job holding by the self‐employed and employed differ?

Abstract: This article considers drivers of second job holding among the self-employed in comparison with the employed. Econometric analysis of panel data explores whether the self-employed are more or less likely to take on a second job when already running their own business than their employed counterparts. The findings contribute to the literature through identification of a need-based variable-difficulty in meeting housing costs-as a key driver of movements from self-employment to hybrid entrepreneurship. Findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…Importantly, self-employed homeworkers indicate that they would like a new job with a new employer, offering some evidence of lower job quality. Self-employed homeworkers are more likely to be women, consistent with the use of home as a workplace due to household constraints and/or lower capitalisation among women-owned SMEs (Atherton et al, 2016). These workers are engaged in a range of different occupations encompassing associate professional, skilled trade and lower-skilled (caring, leisure and personal services, process, plant and machine operatives) jobs.…”
Section: Homeworkersmentioning
confidence: 94%
“…Importantly, self-employed homeworkers indicate that they would like a new job with a new employer, offering some evidence of lower job quality. Self-employed homeworkers are more likely to be women, consistent with the use of home as a workplace due to household constraints and/or lower capitalisation among women-owned SMEs (Atherton et al, 2016). These workers are engaged in a range of different occupations encompassing associate professional, skilled trade and lower-skilled (caring, leisure and personal services, process, plant and machine operatives) jobs.…”
Section: Homeworkersmentioning
confidence: 94%
“…Research on how MJH impacts the work–life interface generally supports the depletion logic. MJHers, particularly those who are primarily self-employed (Atherton, Faria, Wheatley, Wu, & Wu, 2016), report working more hours than SJHers (Bamberry & Campbell, 2012), leaving less time for family. For example, a diary study revealed that because MJHers worked, on average, 2 hr more per day, had more variation in hours, and required longer commutes, they had less time for household activities and leisure than SJHers (Marucci-Wellman, Lin, Willetts, Brennan, & Verma, 2014).…”
Section: A Systematic Review Of the Mjh Literaturementioning
confidence: 99%
“…Two, workers may “job package,” choosing to work a second job or portfolio of jobs to gain flexibility in hours or variety in tasks. Although income targets and job insecurity metrics could be added to the constrained/packaging typology, it can be argued that they are covered within the definitions of these categories (Atherton et al, 2016).…”
Section: Motivations For Multiple Jobholdingmentioning
confidence: 99%